The actualization of Islam Wasathiyah based on the progressive of risalah Islam at Universitas Muhammadiyah Gombong - Tian Khusni Akbar; Ahmad Muslih Atmojo; Muh. Iqbal (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
This research aims to describe and collect information about the actualization of Wasathiyah Islam based on the Risalah Islam Berkemajuan at Universitas Muhammadiyah Gombong. The study is motivated by several aspects, such as the diversity of students from various ethnicities, cultures, languages, and religions, along with the insufficient efforts to implement Wasathiyah Islam within the framework of Risalah Islam Berkemajuan at the university. The research employs a qualitative approach, utilizing data collection techniques such as participatory observation and document analysis through reputable journal sources. The findings indicate that the actualization of Wasathiyah Islam based on Risalah Islam Berkemajuan at Universitas Muhammadiyah Gombong is implemented through various religious activities, including group studies, communal prayers, recitations, and the integration of Islamic values and Pancasila in every course, as well as interfaith dialogue forums. This approach aligns with the progressive nature of the Risalah Islam Berkemajuan concept, illustrating the dynamic and progressive development of Wasathiyah Islamic values in addressing both internal and external challenges, significantly contributing to the enhancement of understanding Wasathiyah Islam within the framework of Risalah Islam Berkemajuan at Universitas Muhammadiyah Gombong.